GAMBARAN PENGETAHUAN ANEMIA, ASUPAN PROTEIN, STATUS GIZI DAN KONSUMSI TABLET TAMBAH DARAH DENGAN ANEMIA PADA SISWI DI SMPN 9 DEPOK - Febriana, Dian; Rahayu, Leni Sri (Program Studi Ilmu Gizi, Jurusan Kesmas Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2025)
Anemia is a significant health issue in Indonesia, particularly prevalent among women of childbearing age and adolescent girls. In Depok, cases reached 34.5% in 2017, highlighting the need for attention. Key nutritional issues linked to adolescent anemia include insufficient protein and iron intake, as well as high consumption of coffee and tea. This study aims to explore the relationship between knowledge of anemia, vitamin C and protein intake, nutritional status, and blood tablet consumption among female students at SMP Negeri 9 Depok. Utilizing a quantitative cross-sectional design, the study sampled 73 students through purposive sampling. Data was collected via questionnaires, 24-hour food recalls, anthropometric measurements, interviews, and blood samples. Results indicated a 37% prevalence of anemia, with 61.6% having inadequate knowledge of anemia and 83.6% reporting low protein intake, while none regularly consumed blood tablets. Statistical analysis revealed no significant relationships between knowledge of anemia (p=0.240), protein intake (p=0.190), nutritional status (p=0.527), and blood tablet consumption regarding anemia incidence. To mitigate anemia, dietary monitoring and support for blood tablet consumption are essential.